Electroless Synthesis of Cobalt Nanowires in Magnetic Field and their Characterization by Resonant Magnetometry Methods - Gegechkori, Tatiana; Mamniashvili, Grigor; Zedginidze, Tinatin; Petriashvili, Tamar (Engineering, Technology & Applied Science Research, 2024)
In this paper, a simple and effective low-temperature electroless chemical method that provides the synthesis of cobalt micro- and nanowires due to the processes of self-organization of magnetic cobalt nanoparticles under the influence of a magnetic field, using the technology of chemical synthesis of magnetic nanoparticles and nanowires is proposed. Cobalt nanoparticles have magnetic dipole moments. An external magnetic field forces them to be oriented parallel to it. Dipole-dipole interactions between magnetic nanoparticles lead to attraction between cobalt nanoparticles leading to their self-organization into nanowires, reducing their total energy. The resulting smaller nanoparticles fill the gaps between the ordered nanoparticles, leading to the formation of smooth cobalt nanowires. The magnetic and structural properties of the synthesized and commercial nanowires polarized by a magnetic field in the epoxy matrix were studied using the resonant radio-frequency magnetometry and electron microscopy methods. These methods are of interest for optimizing the coercive force of cobalt nanowires with a view to their possible use in creating permanent magnets that do not use rare earth elements, as well as in information processing devices and sensors.